AGRICULTURAL INSURANCE ISSUES (World Economics and Finance Bulletin, 2024)
The current state of agricultural insurance in Uzbekistan, the ways of developed and developing countries in agricultural insurance and their current achievements in the development of agriculture in Uzbekistan. There have been made some suggestions on how to minimize the damage and how to financially strengthen farmers, dekhkans and landowners.
Keywords: insurance; insurance losses; reinsurance; calculation